Mellem klasseresignation og kvindeutopi: Om Grete Stenbæk Jensens Konen og æggene og 70’ernes kvindelige arbejderlitteratur - Lund, Nicklas Freisleben (Passage - Tidsskrift for litteratur og kritik, 2025)
“Between Class Resignation and Female Utopia: Grete Stenbæk Jensen’s Konen og æggene and the Female Working-class Literature of the 70s” Centered on analysis of Danish author Grete Stenbæk Jensen’s debut novel Konen og æggene (1973), the article revisits the female working-class literature of the 1970s and argues for the need to re-think the political nature of this often devalued and marginalized chapter of Danish literary history. Thus, the article challenges the widespread preconception of the decade’s working-class literature as ideologically unambiguous and politically agitational by demonstrating how Konen og æggene is characterized by a significant tension between what is conceptualized as the novel’s inherent class resignation and its rudimentary female utopia.